Associação da infecção pelo vírus da hepatite c e pelo vírus da imunodeficiência humana em moçambicanos e brasileiros - Maria da Conceicao Viana Rodrigues (2007)
The prevalence of HIV/HCV co-infection has been reported from Brazil and from some Sub Saharan African countries; however, no data is available from Mozambique. This study aimed at reporting, the prevalence of the co-infection and describe the profile of the selected patients from an Infectious Diseases Unit in Maputo, Mozambique and to compare their profile to a group of patients from a similar Unit in Belo Horizonte, Brazil.We have selected 300 patients from Mozambique and 300 from Brazil, in the age range 18 to 65 years, from November, 2006 to July, 2007. A socio-demographic and epidemiological standard protocol was used to obtain from the volunteers the needed information which was transferred to a data bank and analyzed using the EpiInfo software. Sera from both Mozambique and Brazil were divided into small samples and stored at 20ºC. The HIV infection was diagnosed by, either ELISA or a rapid test, and confirmed by western blot. Hepatitis C was established using the ELISA MEIA (AxSYMG HCV 3.0). PCR (Roche Amplicor 3.0) was applied for confirmation of HCV infection. Sequencing and genotyping (Automatic Sequencer, Applied Biosystem) was used to identify virus subtypes. The prevalence of HIV/HCV co-infection in Mozambique and Brazil was 15.7% and 10.0%, respectively. Also, HIV/HCV co-infection was significantly higher among mozambican women compared to the brazilians and agreeing with the gender distribution of HIV in Mozambique. Behavior risk factors for infection in Mozambicans and Brazilians were, respectively: 0% and 40% for illicit intravenous drug users, 14.9% and 20.0% for blood transfusion, 0.0% and 16.0% for homosexual activity, 100.0% and 76.6% for heterosexual activity, 8.5% and 36.6% for other factors (tattoo,piercing, imprisonment, and occupational risk). Genotypes identified in Mozambique were 1a, 2a, 4 and 5a, whereas, in Brazil they were 1a, 1b and 3a. Our results showed a higher hepatitis C prevalence among Mozambicans as well as an increased frequence among women. The unexpected difference of data about homosexual behavior and use ofintravenous illicit drugs between the study populations raises the issue about the quality of the information obtained in the African country. There was a marked difference in HCV genotype profiles between the two populations. Preliminary analysis revealed that only 8.5% of Mozambicans and 10.0% of Brazilians, HIV/HCV co- infected, fulfilled thecriteria for HCV treatment.